Addressing the origin of highly catalytic activity of A-site Sr-doped perovskite cathodes for intermediate-temperature solid oxide fuel cells - Ziwei Dong; Tian Xia; Qiang Li; Jingping Wang; Shuang Li; Liping Sun; Lihua Huo; Hui Zhao (Electrochemistry Communications, 2022)
Highly active cathode materials are crucial to accelerating the commercialization of intermediate-temperature solid oxide fuel cells (IT-SOFCs). Herein, Sr-doped Pr0.94Ba1-xSrxCo2O5+δ (PBSxCO) perovskite oxides are evaluated by experimental and theoretical studies. The phase transformation from tetragonal layered double perovskite to cubic simple perovskite can be identified with increasing the Sr fraction. Benefiting from enhanced electrical conductivity and oxygen surface rate, the PBSxCO catalysts deliver excellent electrochemical performance, as evidenced by symmetrical and completed cells test. Among all compositions, the Pr0.94Ba0.7Sr0.3Co2O5+δ (PBS0.3CO) cathode has the lowest polarization resistance (Rp) of 0.031 Ω cm2 at 700 °C. The PBS0.3CO cathode-based fuel cell produces a peak power density of 1077 mW cm−2, along with a steady operating for 130 h at 700 °C. From the density functional theoretical (DFT) calculations, it is discovered that stronger Co 3d-O 2p hybridization is recognized in the Sr substituting model compared with undoped one. Furthermore, the decreased free energy for oxygen adsorption may facilitate the oxygen reduction reaction (ORR) kinetics. These findings highlight the origin of optimal ORR activity induced by A-site alkaline earth doping in the perovskite catalysts, endowing the rational design of oxide catalysts.